Fresh takes on five health data sharing domains: Quality, privacy, equity, incentives, and sustainability - Guerrini, Christi J.; Majumder, Mary A.; Robinson, Jill O.; Cook-Deegan, Robert; Blank, Matthew; Bollinger, Juli; Geary, Janis; Gutierrez, Amanda M.; Shrikant, Maya; McGuire, Amy L. (Frontiers in Big Data, 2023)
As entities around the world invest in repositories and other infrastructure to facilitate health data sharing, scalable solutions to data sharing challenges are needed. We conducted semi-structured interviews with 24 experts to explore views on potential issues and policy options related to health data sharing. In this Perspective, we describe and contextualize unconventional insights shared by our interviewees relevant to issues in five domains: data quality, privacy, equity, incentives, and sustainability. These insights question a focus on granular quality metrics for gatekeeping; challenge enthusiasm for maximalist risk disclosure practices; call attention to certain power dynamics that potentially compromise the patient’s voice; encourage trust in the sharing proclivities of new generations of scientists; and endorse accounting for personal disposition in the selection of long-term partners. We consider the merits of each insight with the broad goal of encouraging creative thinking to address data sharing challenges.